Proyecto de factibilidad para la creación de una empresa dedicada a hacer modificaciones tipo tuning y afines en la parte exterior de autos livianos, en el sector del condado de la ciudad de Quito. - Regalado Padilla, Cristian Andrés (2013)
In this paper we developed a business plan with the aim of creating a company dedicated to the provision of services, these will only car modification, straighten and painting for all kinds of vehicle provided they are in the category of vehicles light, located in the area of the County town of Quito. We analyzed the Ecuador economy and economic indicators. I can also perform a study of the automotive industry and global Ecuadorian The market, which allowed us to perform an analysis of the population which will target our service, analyzing tastes, preferences, frequency of use of customer service. Legal study was conducted to examine the documentation for the company.